Tingkat Kompetensi Tenaga Administrasi Sekolah dalam Memanfaatkan ICT (Studi kasus di Sekolah Dasar Kabupaten Bener Meriah – Aceh) - Iskandar, Iskandar; Alfi, Syahrin; Riskan, Abqa; Hasan, Basri (peusangan, 2023)
This research aims to determine and quantitatively describe the level of competency with a focus on the technical abilities of School Administrative Staff (TAS), both in managing and processing personnel data, student data, correspondence and archives by utilizing Information and Communication Technology (ICT). The research was conducted by survey on a sample of 40 TAS with a questionnaire instrument, and data analysis techniques used descriptive statistical analysis. The results of the research obtained an overview of TAS’s ability level scores which describe its technical competence in processing, processing and administering data, namely: 1) TAS’ level of competence in utilizing ICT for personnel data, student data, as well as correspondence and archival matters, with a total average of between 6.90 to 7.54. The use or utilization of ICT varies, manually (19.6%), using Microsoft Excel software (34.4%), using e-school (online web-based 33.3%), and applications connected to mobile devices (12, 7%).